Alternative Dispute Resolution Model Based On Local Wisdom In Settlement Of Land Dispute In Alor Regency - Rade, Stefanus Don; Geme, Maria Theresia; Peter Lay, Benediktus (UNIVERSITAS PAKUAN, 2022)
This research is to respond to the problem of land disputes in the issue of land boundary designation and inheritance distribution in the community of Maru Village, which prefers to resolve land dispute problems using local wisdom patterns as a form of settlement through non-litigation channels and applicable in the Maru Village community Because according to the village community, accommodation using local wisdom patterns is more effective, the settlement process is more straightforward and more practical. This study aims to describe the types and characteristics of land disputes in the last five years and dispute resolution efforts based on alternative dispute resolution (ADR) based on local wisdom. The problem in this study is the characteristics of law in the local knowledge of the Maru community. The chosen approach is a variation between normative and empirical research, so the historical, conceptual, philosophical, and case techniques are preferred. The method offered as a form of alternative dispute resolution (ADR) is an effort to resolve using customary traditions and customary law of Maru Village, namely Hari. The resulting research results are the settlement process using customary law and local wisdom in Maru Village in the field of law, especially land and inheritance cases in the form of settlement efforts in the form of adjudication, conciliation, and customary law, namely Hari, which will undoubtedly have an impact on reducing (litigation lawsuits) because non-litigation settlements have been carried out with the ADR model